Testing The Weak-Form Efficiency For Sixteen Arab's Stock Markets - حساني, عبد الرزاق; البني, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Financial markets play an important role in financing investments and economic growth, therefore, these markets must be efficient. Market efficiency is the most important feature of financial markets, which is an indicator of its success, strength and reflects pricing fairness of the traded stocks. Hence, no investor can beat the market and gain abnormal returns. This study aims at testing the weak form efficiency for the stock markets in (Syria, Lebanon, Jordan, Palestine, Iraq, Saudi Arabia, Kuwait, Dubai, Abu Dhabi, Qatar, Oman, Bahrain, Egypt, Tunisia, Algeria, and Morocco) by using daily returns for these markets Index over period from the beginning of 2010 till the end of February 2020, by applying many statistical tests namely: Normality, Auto correlation, Unit Root by using ADF, Runs Test and Variance Ratio Test. The empirical results showed that the stock markets in (Syria, Lebanon, and Kuwait) are efficient in the weak form of efficiency, but the stock markets in (Jordan, Palestine, Iraq, Saudi Arabia, Dubai, Abu Dhabi, Qatar, Oman, Bahrain, Egypt, Tunisia, Algeria, and Morocco) are not efficient in the weak form of efficiency. This study comes up with a few recommendations to the authorities and entities of these markets in order to lift up the level of market efficiency, by activating all methods of delivering the information to all market participants at the same time without cost, and facilitate entering new companies to the markets.